2020
DOI: 10.13031/trans.13709
|View full text |Cite
|
Sign up to set email alerts
|

Denitrifying Bioreactor Woodchip Recharge: Media Properties after Nine Years

Abstract: HighlightsWood media harvested from a nine-year-old denitrifying bioreactor were evaluated.Media physical changes had multiple causes and effects.Impacts of the physical changes may have been exacerbated by development of preferential flow.LCIs > 0.6 showed C quality declined but media still supported N removal.Abstract. There is a lack of information on denitrifying bioreactors treating subsurface drainage water at the end of their initial design life due to the relative newness of the technology and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Due to the controlled conditions at the Iowa State Research Farm, the observed subsidence is not likely attributable to damage by field equipment. Sedimentation is also unlikely in this system because of the use of a reservoir tank prior to the inlet into the bioreactors, although others have hypothesized sedimentation was occurring based on an increase in the proportion of media particles falling under 1.18 mm and an increase in observed ash content (Christianson et al., 2020; Feyereisen & Christianson, 2015; Ghane et al., 2018; Robertson et al., 2008).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Due to the controlled conditions at the Iowa State Research Farm, the observed subsidence is not likely attributable to damage by field equipment. Sedimentation is also unlikely in this system because of the use of a reservoir tank prior to the inlet into the bioreactors, although others have hypothesized sedimentation was occurring based on an increase in the proportion of media particles falling under 1.18 mm and an increase in observed ash content (Christianson et al., 2020; Feyereisen & Christianson, 2015; Ghane et al., 2018; Robertson et al., 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, Christianson et al. (2020) reported a decrease in D50 over 9 yr. Both these studies also indicated a decrease in porosity, likely from sedimentation as subsidence was not reported.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For the evaluation of the hydraulic performance, the parameters, which purely target at preferential flow (e.g., S or λ), should be preferred compared to parameters, which also target at dispersion (e.g., MDI). In this case, the resulting S-value of 0.56 indicates moderate short-circuiting in the third drainage season; it is likely that some pore water regions in the woodchips are more mobile than others (caused for example by local compaction or bio-clogging) and this might also change further over time as the woodchips are being decomposed, which in turn leads to a change of the pore network and the saturated hydraulic conductivity [17]. In this particular case, the minimum residence time due to short-circuiting was still sufficiently long for the nitrate removal, but for bioreactors with shorter t n , the replacement of the woodchips after several years might be more necessary due to hydraulic malfunctions than due to carbon-supply limitations [17].…”
Section: Hydraulic Conditions In the Woodchip Bioreactormentioning
confidence: 99%
“…During the remaining months, the denitrification was complete and only N org was released from the woodchip bioreactor. However, compared to TOC, the release potential of the bioreactor for N org is low due to the high C/N ratio (>200 [17]) of the woodchips. In the drainage season 2019/2020, the N org -load in the outflow was only increased by 4% compared to the inflow, while for TOC an increase of 45.6% was observed.…”
Section: Impact Of the Woodchip Bioreactor On Nutrient Loads (N O-pomentioning
confidence: 99%